Frame Loss Effects on Visual Fatigue in Super Multi-View 3D Display Technology - Fang, Hongjin; Chen, Yu; Teng, Dongdong; Luo, Jin; Wu, Siying; Zheng, Jianming; Wang, Jiahui; Chen, Zimin; Liu, Lilin (Electronics (Basel), 2024)
Super multi-view (SMV) display is a promising 3D display technology; however, potential frame loss due to bandwidth-limited video transmission could cause discomfort to viewers. Thus, an evaluation of the acceptable viewing experience will be valuable. This study investigates the effects of frame loss on visual fatigue in SMV display, focusing on quantified frame loss rates and varying frame loss modes. Experiments were conducted with 20 subjects, utilizing the Stroop test through an SMV display system to evaluate the visual fatigue under different frame loss conditions. The results show a rise in visual fatigue as the frame loss rate increases, with two critical thresholds identified. A 4% frame loss rate marks the threshold for significant loss-induced differences, beyond which visual fatigue begins to become significant in loss-induced modes compared to the normal loss-free mode. Subsequently, a 10% frame loss rate marks the threshold for significant mode-dependent differences, beyond which variations appear between different loss-induced modes, with monocular mode inducing more visual fatigue than binocular and dual-view more than single-view. Consequently, the findings advocate for refining the 3D video processing to maintain a frame loss rate below 4% for negligible effect and considering the interactions between different views for less visual fatigue. This research aims to provide insights and guidance for addressing potential challenges in developing and applying SMV display technology.